Perseguição e fuga em modelos presa-predador - Silveira, Priscila Azevedo da (2010)
The main purpose of this dissertation is to propose and analyze the effects of pursuit and evasion on predator-prey spatiotemporal dynamics. We use a Coupled Map Lattices formulation in which a system of difference equations is coupled by dispersal. We consider that prey population present density dependent growth and suffer linear predation. Predators go to extinction in the absence of preys. In order to analyze the effects of taxis movement on the results of the model, we initially present a simple diffusion scheme for dispersal. Then, we formulate a dispersal rule that takes into account only local information, which leads to a taxis ux. Finally, in order to describe a quasi-local search, that is, when ndividuals collect information in a neighborhood of their current position, we present a third scheme of movement. We developed numerical simulations for several parameter sets and different combinations of the dispersal scheme and compared the results. We conclude that the dispersal behavior of predators and preys plays a crucial role on their spatiotemporal dynamics and hence can not be omitted when modeling predator-prey interactions.